EFEK MEDIASI KOMPENSASI DALAM HUBUNGAN GAYA KEPEMIMPINAN DENGAN KINERJA PEGAWAI PADA SUKU DINAS BINA MARGA KOTA ADMINISTRASI JAKARTA SELATAN - Noviyudin, Noviyudin; Hidayat, Syamsul (Jurnal Manajemen, 2018)
This study aims to determine the influence of leadership style on compensation; the influence of leadership style on employee performance; the effect of compensation on employee performance and the influence of leadership on performance through compensation in the Sub-Department of Highways Administration of South Jakarta Municipality. The population in this study amounted to 260 employees, using Simple Random Sampling. The sample collected are 72 respondents. The analysis method used in this research are descriptive method and Path Analysis. The results showed that leadership style has no significant effect on compensation; The leadership style has a positive but insignificant effect on performance; compensation has a positive and significant effect  on performance, and leadership style has a positive and significant influence on performance through compensation.